Simulation Uncertainty of Near-Surface Wind Caused by Boundary Layer Parameterization Over the Complex Terrain - Chen, Luyuan; Li, Guangwei; Zhang, Feimin; Wang, Chenghai (Frontiers in Energy Research, 2020)
Accurate prediction of near-surface wind based on numerical weather prediction models is essential to promote efficient wind energy harvesting. In this study, the performances of different Boundary Layer (BL) schemes in Weather Research and Forecasting model on the simulation of near-surface wind over complex terrain are investigated. Results indicate that, 1) the observed mean wind speed, its standard deviation and wind power density are evidently larger in Spring (seasonal shift period) than that in other season, with the maximum in April 2008; 2) YSU scheme produces overall higher prediction accuracy of near-surface wind speed, wind power density and ideal energy production than the other schemes, such as MYJ, MYNN, and QNSE, and thus could be regarded as the optimal BL scheme in the research region and the period; 3) further investigations on the simulation results with the YSU scheme suggest that, the simulation of near-surface stability is closely related to the simulation of near-surface wind, however, YSU scheme cannot correctly reflect the daily variation of observed stability in the near-surface layer, which could be the key factor that results in the large simulation errors of near-surface wind, especially during the day-night alternation periods. Overall results imply that using an optimal BL scheme is an effective approach for improving the wind resource utilization and wind power prediction.